Performance of Silica Adsorbent Material for Removing Copper Ions from Produced Water - Karm, Z; Sehud, R.; Dhahir, A. (Technium: Romanian Journal of Applied Sciences and Technology, 2020)
In this study investigation , the utilization silica for removal of copper ions from produced water by the adsorption process. Examination was carried out by studying several parameters like pH solution, adsorbent dosage and contact time. Experiments of adsorption were done at 25 ?C . Copper ions adsorption was very influenced by the pH of solution . The maximum removal efficiency reached (99.99) when the pH was 7. The optimum removal efficiency conditions for Cu2+ using silica are pH 7, contact time 60 min, and dose of silica adsorbent 0.4 mg.